Low-dose in vivo protection and neutralization across SARS-CoV-2 variants by monoclonal antibody combinations - Dussupt, Vincent; Sankhala, Rajeshwer S.; Mendez-Rivera, Letzibeth; Townsley, Samantha M.; Schmidt, Fabian; Wieczorek, Lindsay; Lal, Kerri G.; Donofrio, Gina C.; Tran, Ursula; Jackson, Nathaniel D.; Zaky, Weam I.; Zemil, Michelle; et al. (Nature immunology, 2021)
Prevention of viral escape and increased coverage against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern require therapeutic monoclonal antibodies (mAbs) targeting multiple sites of vulnerability on the coronavirus spike glycoprotein. Here we identify several potent neutralizing antibodies directed against either the N-terminal domain (NTD) or the receptor-binding domain (RBD) of the spike protein. Administered in combinations, these mAbs provided low-dose protection against SARS-CoV-2 infection in the K18-human angiotensin-converting enzyme 2 mouse model, using both neutralization and Fc effector antibody functions. The RBD mAb WRAIR-2125, which targets residue F486 through a unique heavy-chain and light-chain pairing, demonstrated potent neutralizing activity against all major SARS-CoV-2 variants of concern. In combination with NTD and other RBD mAbs, WRAIR-2125 also prevented viral escape. These data demonstrate that NTD/RBD mAb combinations confer potent protection, likely leveraging complementary mechanisms of viral inactivation and clearance. Krebs and colleagues identify multiple mAbs that recognize either the RBD or the NTD of SARS-CoV-2 spike protein that have potent cross-neutralizing activities against variants of concern. Combinatorial mAb cocktails have complementary effects on viral neutralization and Fc effector functions and can protect against SARS-CoV-2 escape mutants.